2016
DOI: 10.1142/s0217984916502869
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on microstructure and martensitic transformation of neodymium-added NiTi shape memory alloys

Abstract: The effect of rare earth element neodymium (Nd) addition on the microstructure and martensitic transformation behavior of Ni[Formula: see text]Ti[Formula: see text]Nd[Formula: see text] ([Formula: see text] = 0, 0.1, 0.3, 0.5 and 0.7 at.%) shape memory alloy was investigated by scanning electronic microscope, X-ray diffraction and differential scanning calorimetry. The results show that the microstructure of Ni–Ti–Nd ternary alloy consists of NiNd phase, NiTi2 and the NiTi matrix. A one-step martensitic transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In recent years, with the increasing application requirements of materials and the rapid progress of preparation capabilities, the application of materials under some special conditions has attracted attention among many researchers. [6][7][8][9][10] Studies have shown that the addition of Co element to nickel-based alloy causes grain refining, solution enhancement, and the decrease in stacking fault energy, which ensures the material properties of nickel-cobalt alloys. It is believed that the movement of dislocation is the primary deformed mechanism of Ni-Co alloy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the increasing application requirements of materials and the rapid progress of preparation capabilities, the application of materials under some special conditions has attracted attention among many researchers. [6][7][8][9][10] Studies have shown that the addition of Co element to nickel-based alloy causes grain refining, solution enhancement, and the decrease in stacking fault energy, which ensures the material properties of nickel-cobalt alloys. It is believed that the movement of dislocation is the primary deformed mechanism of Ni-Co alloy.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, but the addition of Hf and P d can increase the martensitic transformation temperature of N i − T i binary alloys. Moreover, the microstructure and martensitic transformation temperature of the addition of La [9] [10], Ce [11], P r [12], N d [13] [14], Gd [15], Dy [16] to N i − T i binary alloys have been studied using scanning electronic microscopy (SEM), energy dispersive spectrometry (EDS), X-ray diffraction (XRD), and differential scanning calorimetry (DSC). The addition of these rare earth elements to N i − T i binary alloys was found to increase the martensitic transformation temperature and change the phase transformation sequence.…”
Section: Introductionmentioning
confidence: 99%